PENGGUNAAN MEDIA SOSIAL BISNIS DAN ORIENTASI PASAR TERHADAP KINERJA PEMASARAN MELALUI KREATIVITAS PEMASARAN SEBAGAI VARIABEL INTERVENING - Gina ilhami Fatin Fatin; Muh. fahrurrozi; Rohaeniah zain (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2026)
This study aims to analyze the influence of business social media use and market orientation on the marketing performance of MSMEs through marketing creativity as an intervening variable. The study was conducted among 205 MSME operators in East Lombok Regency using a quantitative approach. Data were collected through a questionnaire and analyzed using Partial LeastSquares (SEM-PLS) with the assistance of SmartPLS 4. The results show that the use of business social media and market orientation has a positive and significant effect on marketing creativity and marketing performance. Furthermore, marketing creativity was found to have a positive and significant effect on marketing performance. The results of the mediation test indicate that marketingcreativity mediates the effects of business social media use and market orientation on the marketing performance of MSMEs. This findings suggest that improvements in MSME marketing performance is not only through social media and market orientation, but also marketing creativity as a competitive strategy.